1680-1747 Ottoman Budgets and Deficits Sustainability in a Period of Fiscal Transition: Wars and Administrative Changes - Hakan Berument; Nuray Oguz (Turkish Economic Association, 2004)
This paper studies the sustainability of the Ottoman budget for the period from 1680 to 1747, during different sultanates and war eras. Moreover, we investigate whether the relationship between government revenues and expenditures changes in the period of culus. The empirical evidence gathered in this paper suggests that during the sample period, except for the sultanate era of Mahmut I, the Ottoman budget was not sustainable. The other interesting result of the study is that culus payments had a significant tax increasing effect. Moreover, the distribution of culus deteriorated the sustainability of budget.
Keywords: N43; N45; E62; 330; Budget sustainability; Structural factors; Ottoman Empire